Effectiveness of Pro-Arginine Containing Eggshell Toothpaste in Occluding Dentinal Tubules: A Comparative Study - Manchem, Aishwarya; Mohammad A K Nawaz; Borugadda, Roopesh; Neelima, U Lavanya; Kondipudi, Nimisha; Palla, Likitha (International Journal of Dental Materials, 2024)
Background: Dentin hypersensitivity, a prevalent condition characterized by acute pain from exposed dentin, can significantly impact quality of life. Treatments often involve occluding dentinal tubules or modulating pain responses. Recent interest in natural products has led to investigating the efficacy of eggshell powder combined with arginine for managing this condition. Aim: To evaluate and compare the effectiveness of three different toothpaste formulations—Pro-Arginine Containing Eggshell Toothpaste (PA-ESTP), Eggshell Toothpaste (ESTP), and Pro-Argin™-Formulated Toothpaste—in occluding dentinal tubules and alleviating dentin hypersensitivity. Materials and methods: Thirty human maxillary premolar teeth were prepared into dentin discs, etched, and treated with one of the three toothpaste formulations. A standardized brushing protocol was simulated using a powered toothbrush. Dentin tubule occlusion was analysed using Scanning Electron Microscopy (SEM) to assess the number of open, partially closed, and completely closed tubules. ANOVA was used to examine differences in tubule occlusion among the three groups. Results: PA-ESTP demonstrated superior performance with 85.51 ± 1.33 completely closed tubules and significantly fewer open tubules than ESTP and Pro-Argin™-Formulated Toothpaste. Statistical analysis confirmed these differences were significant (p < 0.001). Conclusion: Pro-Arginine Containing Eggshell Toothpaste (PA-ESTP) is more effective in managing dentin hypersensitivity than the other tested formulations. The combination of arginine and eggshell powder enhances tubule occlusion, offering a promising treatment option. Further, clinical trials are needed to confirm these findings and evaluate long-term efficacy.